Pengaruh Disiplin Kerja, Reward dan Punishment Terhadap Kinerja Karyawan Bagian Gudang DC Sakinah Surabaya - Dyah Aprelia; Tri Andjarwati (Manajemen Kreatif Jurnal, 2024)
This research aims to analyze the influence of work discipline, reward and punishment on the performance of employees at the DC Sakinah Surabaya Warehouse. The type of research used is quantitative research. The research method used is to use a questionnaire in Likert scale units. The sampling technique is saturated samples and SPSS 27 as an analysis tool. The data source used is primary data. The sample population is employees of the DC Sakinah Surabaya Warehouse. The sample consists of 40 respondents. The validity test of the instrument uses Pearson correlation, while the reliability test uses Cronbach Alpha, and data analysis is carried out using multiple regression analysis techniques. The results of the research show that work discipline has a positive and significant effect on the performance of employees at the DC Sakinah Surabaya Warehouse, rewards have a positive and significant effect on the performance of employees at the DC Sakinah Surabaya Warehouse, punishment has a positive and significant effect on the performance of employees at the DC Sakinah Surabaya Warehouse. Work discipline, reward and punishment partially or simultaneously influence the performance of employees at the DC Sakinah Surabaya Warehouse.